Learning together: Experimental evidence on the impact of group-based nutrition interventions in rural Bihar - Raghunathan, Kalyani; Kumar, Neha; Gupta, Shivani; Chauhan, Tarana; Kathuria, Ashi Kohli; Menon, Purnima (Elsevier, 2023)
India accounts for a large proportion of the global prevalence of maternal and child undernutrition, and recent trends have renewed the call for large-scale concerted efforts to improve outcomes. With their reach to millions of rural Indian women, self-help groups (SHGs) offer a possible solution. We provide evidence from a cluster-randomized controlled trial in the state of Bihar of the impact of a health and nutrition intervention that provided behavior change communication to SHG members and worked to strengthen utilization of services. Over the course of 2.5 years, the intervention resulted in a 7% increase in the number of food groups consumed by children and a 30% increase in the proportion of women achieving minimum dietary diversity but had no impact on women’s body mass index or child underweight and wasting. Both knowledge and adoption of key behaviors along the impact pathway improved as a result of the treatment. SHGs certainly have the potential to effect social change and accelerate improvements in maternal and child health and nutrition outcomes, but in resource-constrained settings such as these, information-only interventions delivered through these platforms will likely have limited impact.